Combined effects of Gm or Km immunoglobulin allotypes and age on antibody responses to Plasmodium falciparum VarO rosetting variant in Benin. - Migot-Nabias, Florence; LOKOSSOU, GATIEN; Vigan-Womas, Inès; Guitard, Evelyne; Guillotte, Micheline; Noukpo, Julien M; Mercereau-Puijalon, Odile; Dugougon, Jean-Michel; Garcia, André (My University, 2011)
Clinical protection of Beninese children against Plasmodium falciparum malaria was shown to be influenced by immunoglobulin (IG) Gm and Km allotypes, and related to seroreactivity with the rosette-forming VarO-antigenic variant. IgG to the VarO-infected erythrocyte surface, IgG1 and IgG3 to PfEMP1-NTS-DBL1α(1)-VarO were higher in the under 4-year-old children carrying the Gm 5,6,13,14;1,17 phenotype. In contrast, surface-reactive IgG, total IgG, IgG1 and IgG3 to NTS-DBL1α(1)- and DBL2βC2-VarO domains were lower in the above 4-year-old children harbouring the Km1 allotype. These data outline an age-related association of antibodies against malaria antigens and IG allotype distribution.
Keywords: Allotypes; Immunoglobulin; Plasmodium falciparum